(untitled) (Mazahib, 2025)
This study examines the polemic of al-khurÅ«j ”˜alÄ al-á¸¥ukkÄm (rebellion against rulers) as debated by YÅ«suf al-Qaraá¸ÄwÄ« and Muá¸¥ammad Sa”˜Ä«d Ramaá¸Än al-BÅ«á¹Ä«, particularly in the context of the Syria crisis and the Arab Spring. The theoretical framework employed is maqÄá¹£id al-sharÄ«Ê¿ah, encompassing the hierarchy of maá¹£laá¸¥ah based on á¸arÅ«riyyÄt, á¸¥ÄjiyyÄt, and taá¸¥sÄ«niyyÄt; the preservation of the kulliyyÄt al-khams (religion, life, intellect, lineage, and property); the balancing of conflicting mafsadah; the application of sadd al-dharÄÊ¾iÊ¿ (blocking the means to harm); and the consideration of maÊ¾ÄlÄt (future consequences). Methodologically, the study employs a qualitative textual analysis of fatwa, jurisprudential writings, and theological arguments by scholars, situating their views within the broader maqÄá¹£id framework. Within this framework, al-Qaraá¸ÄwÄ« justifies rebellion against unjust rulers as both a moral duty and a religious obligation to uphold justice, framing it within the maqÄá¹£id imperative of resisting tyranny. Conversely, al-BÅ«á¹Ä« employs the same maqÄá¹£id tools to prohibit rebellion, prioritising the avoidance of bloodshed and societal collapse over immediate political reform. The findings reveal that although both scholars engage maqÄá¹£id al-sharÄ«Ê¿ah, their divergent prioritisation leads al-Qaraá¸ÄwÄ« to emphasise justice and activism as central to preserving Islam’s dignity. At the same time, al-BÅ«á¹Ä« underscores stability and unity as essential safeguards against greater chaos.